(untitled) (Research, Society and Development, 2020)
Tooth erosion or erosive tooth wear is considered a contemporary oral health problem, caused by chemical processes of "acid attack" to the tooth, without bacterial involvement, which causes the loss of mineral structure. This problem occurs in a multifactorial condition, and there may be an interaction between biological, chemical and behavioral factors. In recent years, its prevalence has increased, making it a challenge for dentists, especially when it reaches more advanced stages where it can cause pain, hypersensitivity, problems with function and aesthetics. Through a literature review, the present study aims to guide dental surgeons with information about the history, etiology, diagnosis, prevention and treatment of erosive tooth wear. Knowledge about the etiological factors of erosive tooth wear becomes important to prevent the progression of this problem, in addition to establishing effective preventive measures since childhood. The dental surgeon must perform an early diagnosis and perform the appropriate treatment of this problem, mainly the guidelines regarding food and oral hygiene in addition to fluoride therapies.